Pengaruh Tingkat Pendidikan dan Jenis Kelamin Peternak terhadap Tingkat Produksi Babi (Studi Kasus di Manokwari, Papua Barat Indonesia) - Deny Anjelus Iyai; Stepanus Pakage; Agustinus G Murwanto; Maria Arim; Dwi Nurhayati; M Lily Orisu; Isti Widayati; Hieronymus Yohanes Rumfaan (Jurnal Ilmu Peternakan Terapan, 2020)
The aim of this research was to understand the effect of educational level of gender types on pig farming production, a special case in Manokwari West Papua-Indonesia. The field study was done in Manokwari regency involved six districts. The respondents of 49 farmers chosen guided by local extensions selected from 15 villages. The participatory situation analysis employed to approach pig farmers by using questionnaire. A General Linear Model analysis of variances was used. All data were entered in Excel and analyzed using SPPS version 10.0. The conclusion that interaction between education and gender occur on household member and income earn. The female with adequate education will provide better income than the male. Understanding interaction effect of education level and gender will enable farmers to improve their pig productivities on scales and time.